The Sibylline Relationship Between Human Papillomavirus and Endometrial Cancer: Scarcity of Strong Evidence Linking Both Conditions - Khadija Bichri; Adil El Ghanmi; Fadila Kouhen; Salsabil Hamdi; Karima Fichtali; Fadoua El Mansouri; Jalila El Bakkouri; Bouchra Ghazi (Viruses)
Endometrial cancer (EC) is the fourth-most frequent cancer among the female population and a leading cause of death. Multiple factors are susceptible to causing tumorigenesis, including obesity, lack of physical activity, diabetes mellitus, high concentration of estrogen during menopause, unopposed exposure to estrogen, duration of menses, nulliparity and infertility. Human papillomavirus (HPV) is a double-stranded DNA virus, with certain genotypes exclusively human. HPV plays a major role in some cancers (cervical cancer, head and neck cancer, lung cancer, and anogenital cancers). Given the intricate correlation between HPV and cervical cancer, the scientific community conjectured that HPV may be implicated in the carcinogenesis of the endometrium. In this review, we will direct our interest towards previous studies that focused on the expression of HPV on EC samples and cover how both conditions might connect to each other.